INTROGRESSION BREEDING – EFFECTS AND SIDE EFFECTS OF MARKER-BASED INTRODUCTION OF TWO NON-ADAPTED QTL FOR FUSARIUM HEAD BLIGHT RESISTANCE INTO ELITE WHEAT - Miedaner, T.; von der Ohe, C.; Korzun, V.; Ebmeyer, E. (Plant Breeding and Seed Science, 2011)
Fusarium head blight resistance (FHB) can be achieved by using improved adapted varieties as crossing partners or by a marker-assisted introgression of mapped QTL from non-adapted sources. In this long-term study Fhb1 on chromosome 3BS and Qfhs.ifa-5A located on chromosome 5A were introgressed into European elite spring and winter wheat to test effects on FHB resistance and side effects on agronomic performance and F. graminearum isolates and mixtures. The introgression of the QTL Fhb1 and Qfhs.ifa-5A from the Sumai 3-descendant CM82036 could be performed in the shortest possible way by marker-assisted backcrossing. They were both validated in European elite wheat background. Effects on FHB resistance were, on average, only about half of the effect in the original mapping populations. In the best phenotypically and marker-selected BC0 line of spring wheat FHB was reduced from 40 to 4.3% of disease symptoms by introgressing both QTL, in the best BC3 line of winter wheat the reduction was 28 and 37% for the moderately resistant and highly susceptible recurrent parent, respectively. Introgression of both QTL simultaneously did not result in significantly higher FHB resistance than introgression of only one of both QTL. Small significant negative effects on grain yield were detected in the Anthus but not in the Opus BC3F2:5 backcross population when both QTL were introgressed. Backcrossing with only Qfhs.ifa-5A did not reduce grain yield significantly. Differences in heading date, plant height and quality traits were in all cases small although often significant. Selection of lines with improved resistance level and similar high yield level like the recurrent parent was feasible. Stability of FHB resistance mediated by both QTL was stable across 22 Fusarium isolates from Europe and Canada and six binary mixtures. Competition effects between isolates in mixtures were obvious but could not be attributed to the resistance of the host. In conclusion, marker-based backcrossing is a feasible option for introgressing Fhb1 or Qfhs.ifa-5A QTL into the high-yielding, quality-oriented European wheat gene pool.